2014
DOI: 10.1007/s10753-014-9817-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyane-carvone, a Synthetic Derivative of Carvone, Inhibits Inflammatory Response by Reducing Cytokine Production and Oxidative Stress and Shows Antinociceptive Effect in Mice

Abstract: Cyane-carvone (CC) was studied to elucidate its anti-inflammatory, antinociceptive, and antioxidant effects in Mus musculus. Anti-inflammatory (bradykinin, histamine, prostaglandin E2, serotonin, and carrageenan) and antinociceptive (acetic acid and formalin) models were utilized. Myeloperoxidase activity, interleukin (IL)-1β, tumor necrosis factor alpha (TNF-α), and glutathione (GSH) levels were evaluated. Analysis of variance followed by Student-Newman-Keuls' test was done. Results were compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Cell migration into the site of injury, erythema, oedema, pain, and fever are clinical signs of inflammation and symptoms. The release of pro-inflammatory cytokines, such as tumour necrosis factor-α (TNF-α), activated by macrophages, leads to vascular endothelial cell activation and causes leukocytes to migrate to the inflamed region (7).…”
Section: Introductionmentioning
confidence: 99%
“…Cell migration into the site of injury, erythema, oedema, pain, and fever are clinical signs of inflammation and symptoms. The release of pro-inflammatory cytokines, such as tumour necrosis factor-α (TNF-α), activated by macrophages, leads to vascular endothelial cell activation and causes leukocytes to migrate to the inflamed region (7).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory activity of cyane–carvone (CC), a monocyclic monoterpene, was evaluated by the methods of bradykinin, histamine, prostaglandin E 2 (PGE 2 ), serotonin, and carrageenan-induced paw edema in mice [ 34 ]. It was found that in bradykinin, histamine, PGE 2 , and serotonin tests, 75 mg/kg CC significantly decreased paw edema (t = 30, 60, 90, and/or 120 min).…”
Section: Resultsmentioning
confidence: 99%
“…The antiproliferative mechanism of action has also been elucidated. Moreover, some studies proved the anti-inflammatory property of carvone and investigated the underlying molecular mechanism [ 33 , 34 , 35 , 36 ]. Anticancer mechanisms of carvone are due to its different actions against checkpoints of cancer cells such as inducing apoptosis and cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on carvone derivatives also demonstrated their anti-inflammatory potential [18]. de Sousa et al reported that orally administered hydroxydihydrocarvone exerted anti-inflammatory effects in rats and mice [21,22]. Marques et al studied the anti-inflammatory activity of cyane-carvone, a synthetic derivative of carvone, and found that it significantly decreased IL-1β and TNF-α levels and significantly inhibited paw edema in mice [22].…”
Section: Bioactivity Profile Of Seo In the Human Dermal Fibroblast Symentioning
confidence: 99%